Detection of terpenes of Iraqi Artemisia abrotanum L. by GC/MS in hexane extract - Omar Salim Aruba; Gaith Ali Jasim; Abdulmutalib A. Nasser (College of Pharmacy / Mustansiriyah University, 2019)
Artemisia abrotanum L. is recently introduced plant in Iraq, in this study we conducted GS/MS for detection of terpene that are group of constituents abundant in this species qualitatively and quantatively. We used hexane extract for the detection depending on the like dissolve like proce-  dure of extraction since they are mostly nonpolar compounds, they dissolve in nonpolar solvent like hexane thus the extraction procedure is conducted with this solvent. New compound was detected with hexane extract that wasn't present in previous studies.